"If it's already tough, imagine for me..." : A Qualitative Perspective on Youth Out of School and Out of Work in Brazil - Machado, Ana Luiza; Muller, Miriam (World Bank, Washington, DC, 2018)
Drawing on in-depth interviews with young women and men in rural and urban Brazil, this qualitative research explores gender dimensions in the causes and consequences of being "out of work and out of school." A key conclusion from this research is that this term (or the Portuguese: "nem-nem") does not translate well the complex realities of this highly heterogeneous group. The paper develops inductively from the data a typology of these youth, who face different barriers along their trajectories: a) barriers to building aspirations and internal motivation to return to school or work, b) barriers to action, and c) external barriers. Participants' position along this spectrum is shaped by social context and gender norms that frame youth's trajectories and envisioned futures. These observed patterns are particularly strong in rural areas, where youth perceive fewer quality economic opportunities and stronger division of gender roles within the household and in farming activities, which keeps young women in lower paid or unpaid roles. Participants who have successful trajectories to technical schools, universities, or formal work demonstrate strong resilience, which seems to be built on their relationships with their families, peers, partners, and role models.